Water stress index on sugarcane in different developmental phases - Brunini, Rodrigo Garcia [UNESP] (2018)
Brazil is the world leader in the production of sugar and ethanol due to its intensive cultivation of the sugarcane crop, mainly in the Southeast region of the country. However, its expansion into other areas has gained strength in recent years and has caused significant variations in the harvest due to problems related to the climate of the region. The use of water stress indexes in the developmental phases of the crop can be an essential tool for irrigation control, preventing the negative effects of water stress on the plants. The aim of this study was to determine the ideal time to irrigate a sugarcane crop, using a water stress index found using infrared thermometry. The research was developed in an area called the “Experimental Hydrographic Basin” and employed surfaces with different slopes (0% to 40%) and solar exposures (North, South, East and West), under an induced water deficit. The analyses were performed in the field and in the laboratory. The results of this study indicate that the ideal time for irrigation differs for each phase of sugarcane development, in a range between 2.0 °C and 5.0 °C, and is more critical in the tillering phase. A surface maintained at field capacity had a lower water stress index and a higher productivity (124 Mg ha−1).